REKONSTRUKSI MODERASI BERAGAMA DALAM KURIKULUM PENDIDIKAN ISLAM: ANALISIS EFEKTIVITAS IMPLEMENTASI NASIONAL - Muhammad Zainudin; Muhammad Sohib; Maftuh (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
Religious moderation is a strategic national agenda aimed at strengthening civic character and preventing radicalism within educational settings. The integration of moderate values into the Islamic Education (PAI) curriculum is expected to cultivate inclusive and tolerant attitudes among students. However, its implementation continues to encounter conceptual and pedagogical challenges that reduce the effectiveness of value internalization. This study aims to analyze the effectiveness of religious moderation implementation in the PAI curriculum and to propose a more contextual and applicable curriculum reconstruction model. This research employs a qualitative approach based on library research, analyzing national policy documents and reviewing empirical studies published within the last five years. No primary field data were collected. Data were examined using content analysis and thematic synthesis to identify implementation patterns, challenges, and opportunities for curriculum improvement.The findings reveal that the implementation of religious moderation in the PAI curriculum remains largely normative and top-down, lacking clear operational pedagogical guidelines and insufficiently supported by teacher capacity development in managing diversity-oriented learning. In addition, school ecosystems that are not yet fully inclusive and limited student digital literacy further hinder the authentic internalization of moderate values.The study concludes that curriculum reconstruction is necessary through strengthening socio-religious competencies, applying dialogical pedagogy, integrating digital literacy, and adopting a whole-school approach to ensure effective and sustainable implementation of religious moderation in the national education system.